Diabetes mellitus type 2 in the elderly - Rymkiewicz, Emilia; Rękas-Wójcik, Agata; Milaniuk, Sylwia; Mosiewicz, Barbara; Dzida, Grzegorz (Polish Journal of Public Health, 2015)
The number of patients with type 2 diabetes increases along with civilizational development. Advanced treatment methods applied in diabetology and other branches of medicine increase the number of patients. The aim of this work is to present diagnostic and therapeutic problems in elderly people with diabetes. There isa a number of other diseases coexisting with diabetes. These are: hypertension, hyperlipidemia and obesity. The risk of diabetes increases with age and it is related to lowered insulin secretion, worsened absorption and insulin resistance. Diabetes symptoms in older patients differ from those of other age groups. An early diagnosis can minimize the risk of any cardiovascular events, ranked as one of the leading causes of death in elderly patients. The choice of treatment should be adjusted to the particular patient’s needs, avoid any sudden modifications of administered drugs and educating the patients. These are the most important elements of the therapy.